2010
DOI: 10.2320/matertrans.mg200906
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Cold-Rolling Texture in a Multi-Layered Material Composed of SUS301 and SUS420J2 Steels

Abstract: A multi-layered composite material composed of alternating SUS301 and SUS420J2 steels, prepared by hot-rolling bonding, shows a superior strength and ductility balance than the components. Few researches have been addressed on texture features of structural multi-layered materials during cold-rolling. In the present work, cold-rolling with three reductions (20%, 40% and 65%) in thickness was conducted on both the two monolithic steels (SUS301 and SUS420J2) and the multi-layered material consisting of SUS301 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, with the increase of hot rolling reduction, the hardness of the TWIP steel layer and 40Si2CrMo steel layer both increased. This was because the number of dislocations in the constituent layers increases, and the packing and winding of dislocations further hinder the movement of dislocations, resulting in work hardening, which increases the hardness of the constituent layer [21,22]. Figure 7 shows the microhardness values of multilayer TWIP/40Si2CrMo steels with different hot rolling reductions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, with the increase of hot rolling reduction, the hardness of the TWIP steel layer and 40Si2CrMo steel layer both increased. This was because the number of dislocations in the constituent layers increases, and the packing and winding of dislocations further hinder the movement of dislocations, resulting in work hardening, which increases the hardness of the constituent layer [21,22]. Figure 7 shows the microhardness values of multilayer TWIP/40Si2CrMo steels with different hot rolling reductions.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the 65% cold rolling of similar multilayered steel composite sheet composed of 13 austenite layers and 12 martensite layers in the sandwich type resulted in the strongest {112}h110i component of martensite texture as well as strong {111}huvwi-fiber and {001}h110i texture components. 24) Because most of martensite blocks are not elongated toward the rolling direction anymore as shown in Fig. 6 and the rotated cube {001}h110i component still exists after the rapid annealing at 1273 K for 120 s in the austenite single phase region of SUS420J2, the partial recrystallization is speculated to take place through the formation of {111}h112i at the expense of {112}h110i component.…”
Section: Resultsmentioning
confidence: 99%
“…The strong {110}h211i component, the strong {110}h001i component and the relative weak {112}h111i-{113}h332i component exhibit the similar annealing characteristics of cold rolled metastable austenite of SUS304 during rapid annealing. 26) Because the 50% cold rolling cannot enable the austenite in SUS301 steel layers to completely transform into martensite, 24) the fine grained equiaxial austenite as shown in Fig. 6 is thought to partially form through the static recrystallization and partially form through the martensite-to-austenite reverse transformation.…”
Section: Resultsmentioning
confidence: 99%
“…1 Multilayered steel with enhanced deformation behaviour and tensile properties consisting of alternating layers of ductile austenitic steel and brittle martensitic steel has been subject to various investigations. [2][3][4][5][6] Inoue et al 2 showed a transition of the fracture behaviour of the martensitic layer from brittle cleavage to ductile shear just by reducing the layer thickness in a hot rolled laminate. More than 50% elongation of as quenched martensite was achieved under tensile loading using a laminated composite consisting of conventional martensitic and austenitic steel.…”
Section: Introductionmentioning
confidence: 99%
“…3 Nambu et al 4 demonstrated tremendous improvement in tensile ductility by increasing the bonding strength in a brittle/ductile multilayered structure. Detailed investigations concerning strain field computation 5 and microtexture development for different cold rolling reductions 6 were carried out for multilayered steel composed of martensitic and austenitic layers. However, no successful welding of that material has been reported so far.…”
Section: Introductionmentioning
confidence: 99%